Scientific Approaches to The Analysis of the Experience of Foreign Countries on the Development of Entrepreneurship in The Service Field - Dilmurod Suyunov; Aman Kenjabaev (Academia One, 2023)
In this article, the role of entrepreneurship in the service sector in ensuring employment and increasing the income of the population is fully covered, and the criteria, indicators and ways of determining them have been developed.
Keywords: entrepreneurship; services; employed population